2008
DOI: 10.1021/la702887m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Magnetic Core−Shell Polymeric Particles

Abstract: A novel synthetic strategy was developed for the preparation of magnetic core-shell (MCS) particles consisting of hydrophobic poly(methyl methacrylate) cores with hydrophilic chitosan shells and gamma-Fe2O3 nanoparticles inside the cores via copolymerization of methyl methacrylate from chitosan in the presence of vinyl-coated gamma-Fe2O3 nanoparticles. The magnetic core-shell particles were characterized with transmission electron microscopy, field-emission scanning electron microscopy, particle size and zeta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…Additionally, polymeric coatings have been engineered to enhance SPION pharmacokinetics, endosomal release, and tailored drug loading and release behaviors. To serve these coating functions, a diverse group of polymers have been investigated including PEG [81, 126, 127, 128, 129, 130, 131, 132], dextran [133, 134, 135, 136], chitosan [137, 138, 139, 140], PEI [104, 141, 142, 143, 144, 145], and phospholipids [145, 146, 147]. …”
Section: Fabrication Of Target-specific Magnetic Nanoparticles (Mnps)mentioning
confidence: 99%
“…Additionally, polymeric coatings have been engineered to enhance SPION pharmacokinetics, endosomal release, and tailored drug loading and release behaviors. To serve these coating functions, a diverse group of polymers have been investigated including PEG [81, 126, 127, 128, 129, 130, 131, 132], dextran [133, 134, 135, 136], chitosan [137, 138, 139, 140], PEI [104, 141, 142, 143, 144, 145], and phospholipids [145, 146, 147]. …”
Section: Fabrication Of Target-specific Magnetic Nanoparticles (Mnps)mentioning
confidence: 99%
“…Mangeney et al reported about the bioreactivity of magnetic Fe 2 O 3 -PS/polypyrrole (PPy) core/shell particles [60]. Ho and Li [61] described magnetic core/shell particles consisting of hydrophobic PMMA cores with γ-Fe 2 O 3 nanoparticles inside. The PMMA cores were encapsulated with hydrophilic chitosan shells.…”
Section: Composite Typesmentioning
confidence: 99%
“…8b). Ho and Li [39] synthesized magnetic core-shell particles via copolymerization of methyl metacrylate from chitosan in the presence of vinyl-coated Fe 2 O 3 nanoparticles. They showed that the terminal double bonds on the vinyl-coated nanoparticles would allow copolymerization between the vinyl groups and methyl metacrylate monomer.…”
Section: Surface Characteristics Of the Nanoparticlesmentioning
confidence: 99%